2014
DOI: 10.1590/1516-3180.2014.1322666
|View full text |Cite
|
Sign up to set email alerts
|

Association between sex hormone-binding globulin (SHBG) and metabolic syndrome among men

Abstract: CONTEXT AND OBJECTIVE: Metabolic syndrome consists of a set of factors that imply increased risk of cardiovascular diseases. The objective here was to evaluate the association between sex hormone-binding globulin (SHBG), sex hormones and metabolic syndrome among men. DESIGN AND SETTING: Retrospective analysis on data from the study "Endogenous oestradiol but not testosterone is related to coronary artery disease in men", conducted in a hospital in São Paulo. METHODS: Men (aged 40-70) who underwent coronary ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…The current study shows that there is no significant difference in serum free testosterone levels between subjects with MetS and non-MetS, which is similar to the findings from other cross-sectional studies [15,16]. Accumulating data have demonstrated that SHBG is more strongly associated with MetS than TT [17,18]. As the score of MetS components increased, the levels of SHBG decreased but SHBG levels were unchanged after addition of five metabolic components.…”
Section: Discussionsupporting
confidence: 90%
“…The current study shows that there is no significant difference in serum free testosterone levels between subjects with MetS and non-MetS, which is similar to the findings from other cross-sectional studies [15,16]. Accumulating data have demonstrated that SHBG is more strongly associated with MetS than TT [17,18]. As the score of MetS components increased, the levels of SHBG decreased but SHBG levels were unchanged after addition of five metabolic components.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies suggest that SHBG, as a sex hormonebinding and transport molecule, can better reflect changes in sex hormone levels. 12,14 Similarly, a correlation between sex hormone changes and BPH was also found in rabbits on an HFD diet, and receptors for sex steroids were all increased in the prostates of rabbits fed an HFD, suggesting that in MetS, the sensitivity to changing gonadal hormones is upregulated. 26 This might explain how MetS affects PV through sex hormones.…”
Section: Furthermore As Shown Inmentioning
confidence: 74%
“…In the present study, logistic regression analysis showed that SHBG alone had a weak association with the risk of BPH in the hormone‐adjusted model ( P = .048). Some studies suggest that SHBG, as a sex hormone‐binding and transport molecule, can better reflect changes in sex hormone levels 12,14 . Similarly, a correlation between sex hormone changes and BPH was also found in rabbits on an HFD diet, and receptors for sex steroids were all increased in the prostates of rabbits fed an HFD, suggesting that in MetS, the sensitivity to changing gonadal hormones is upregulated 26 .…”
Section: Discussionmentioning
confidence: 98%
“…It controls the transport of sex steroid hormones in the blood circulation to their target tissues 13. Many previous studies have revealed that low levels of serum SHBG are associated with metabolic syndrome, type II diabetes, and cardiovascular disease 45. Nonalcoholic fatty liver disease (NAFLD) grade is also known to be inversely related to serum SHBG levels:67 as the grade of hepatic steatosis increases, serum SHBG level decreases 27.…”
Section: Introductionmentioning
confidence: 99%